Effects on mouse melanoma and immune cells of P2X7 receptor positive allosterism by clemastine - Maria Luiza Thorstenberg; Simonetta Falzoni; Rocio Edith Garcia-Jacobo; Leticia Scussel Bergamin; Mario Tarantini; Giulia Conversano; Anna Pegoraro; Francesco Di Virgilio; Elena Adinolfi; Anna Lisa Giuliani (Purinergic Signalling, 2026)
Clemastine (CLE), an H1R antagonist widely used for the treatment of allergic rhinitis, has recently been investigated for its positive modulatory effects on P2X7, a receptor for extracellular ATP (eATP) involved in the regulation of inflammation, immune responses, and the composition of the tumor microenvironment (TME). Here, we further examined the effects of CLE on P2X7-mediated responses to clarify the pharmacological significance of P2X7 potentiation. First, in murine and human cells expressing (B16F10 WT and HEK293-hP2X7) or lacking (B16F10 P2X7 −/− and HEK293 WT) the P2X7 receptor, we measured intracellular Ca 2+ influx, ethidium bromide (EB) and daunorubicin (DN) uptake, mitochondrial morphology, and LDH and ATP release following P2X7 agonism or antagonism in the presence of CLE. We found that CLE increased Bz-ATP-induced P2X7-mediated channel opening, pore formation, mitochondrial remodeling, eATP release, and cell death, effects absent in P2X7-null cells and abolished by P2X7 antagonists. As a readout of activation of NLRP3 inflammasome, a known downstream effector of the P2X7 receptor, we also assessed the effect of CLE on IL-1β release from peritoneal macrophages from wild-type (WT) or P2X7 knockout (KO) mice, LPS-primed and treated with ATP and/or CLE. We found that the combined treatment significantly increased IL-1β release from P2X7-WT macrophages compared to the two stimuli administered separately. On the whole, our results demonstrate that CLE can effectively positively modulate P2X7 function, suggesting new opportunities for its therapeutic exploitation.